Effects of variety and sett weights on sprout emergence and seed tuber yield in Dioscorea alata L. and Dioscorea rotundata Poir - Pelemo, O.; Okolie, O.C.; Olaniyan, A.B.; Agre, A.P.; Balogun, M.; Maroya, N.; Akoroda, M.; Asiedu, R. (MDPI, 2025)
Yam is a staple crop in Africa that is constrained by its low multiplication rate. This results in a short supply of seed tubers, which is a challenge to increased production. This study assessed the influence of different minisett weights (10, 20, 30, 40, and 50 g) on tuber production and seed categorization in twelve Dioscorea rotundata and four Dioscorea alata varieties over two planting seasons in a Randomized Complete Block Design (r = 3). The yield parameters were collected and analyzed using ANOVA. The effects of varieties, the minisett weight (SW), and the variety × SW interaction were significant for the proportion of setts that produced seed tubers and ranged from 40.2 ± 5.0% (50 g) to 56.4 ± 5.0% (10 g) in 2013, from 46.4 ± 0.8% (40 g) to 60.5 ± 0.8% (30 g) in 2014, from 23% (TDa00/00194, 30 g) to 93.7% (Ojuyawo, 10 g) in 2013, and from 39.7% (TDa00/00194, 30 g) to 100% (TDr89/02665, 20 g) in 2014. The 10 g and 30 g produced more seed yam in 2013 and 2014, respectively, while 50 g produced more ware yam sizes (>300 g) and is thus recommended to farmers for intended yam production category. D. rotundata varieties produced a higher proportion of seed yam, while D. alata varieties produced are a higher proportion of yams above seed class.